Tax collection obstacle resolution strategy and taxpayer profile validity: Case study: KPP Madya Palembang - Fenta, Nadya Diti; Tresnajaya, Rd. Tatan Jaka (WIM Solusi Prima, 2025)
This study aims to analyze the obstacles in the tax collection process and the validity of taxpayer profiles at KPP Madya Palembang. This research is motivated by significant challenges in achieving national revenue targets, particularly in resolving tax collection arrears. The study employs a qualitative method with a case study approach to explore the phenomenon in depth. Primary data were obtained through interviews with four informants, while secondary data were gathered through literature reviews and document analysis to provide a comprehensive perspective. The findings reveal three main categories of tax collection obstacles: technical, administrative, and potential future challenges. Technical obstacles are related to practical and operational issues in the field, administrative obstacles include procedural and administrative processes, while future challenges involve limited resources and preparations for Coretax 2025. Proposed strategies include regularly updating taxpayer data, enhancing inter-agency coordination, and implementing automated tax collection systems. The novelty of this research lies in the specific categorization of obstacles into three main categories analyzed in an integrated manner, as well as an in-depth exploration of the relationship between taxpayer profile validity and tax collection effectiveness using recent data (2021–2023). Furthermore, the study’s focus on a specific location, KPP Madya Palembang, provides contextually relevant recommendations. This study concludes that synergy between addressing tax collection obstacles and ensuring the validity of taxpayer data is crucial to sustainably increasing national revenue while supporting efficient and transparent fiscal management practices.